PENGARUH PROFITABILITAS, COLLATERALIZABLE ASSETS, INVESTMENT OPPORTUNITY SET, DAN LAGGED DIVIDEND TERHADAP KEBIJAKAN DIVIDEN - Retno Suliati Suleiman; Mila Permatasari (GoAcademica Research dan Publishing, 2022)
This study aims to determine the effect of profitability, collateralizable assets, investment opportunity set, and lagged dividend on dividend policy. The sample companies were selected using the purposive sampling technique. After selecting the sample, a sample of 35 samples from 7 companies was obtained multiplied by a 5 year period. The analysis in this study uses normality test, classical assumption test, hypothesis test, coefficient of determination and multiple linear regression analysis. Based on the results of the study, it can be concluded that: 1) profitability, collateralizable assets, investment opportunity set, and lagged dividend all have the same effect on dividend policy, with an adjusted R square value of 62.3%; 2) profitability has no effect on dividend policy; 3) assets that can be pledged as collateral have no effect on dividend policy; 4) investment opportunity set has no effect on dividend policy; and 5) lagged dividend has a positive effect on dividend policy.